Molecular insights into alginate β‐lactoglobulin A multivalencies—The foundation for their amorphous aggregates and coacervation. (18th January 2023) - Madsen, Mikkel; Prestel, Andreas; Madland, Eva; Westh, Peter; Tøndervik, Anne; Sletta, Håvard; Peters, Günther H. J.; Aachmann, Finn L.; Kragelund, Birthe B.; Svensson, Birte
Abstract: For improved control of biomaterial property design, a better understanding of complex coacervation involving anionic polysaccharides and proteins is needed. Here, we address the initial steps in condensate formation of β‐lactoglobulin A (β‐LgA) with nine defined alginate oligosaccharides (AOSs) and describe their multivalent interactions in structural detail. Binding of AOSs containing four, five, or six uronic acid residues (UARs), either all mannuronate (M), all guluronate (G), or alternating M and G embodying the block structural components of alginates, was characterized by isothermal titration calorimetry, nuclear magnetic resonance spectroscopy (NMR), and molecular docking. β‐LgA was highly multivalent exhibiting binding stoichiometries decreasing from five to two AOSs with increasing degree of polymerization (DP) and similar affinities in the mid micromolar range. The different AOS binding sites on β‐LgA were identified by NMR chemical shift perturbation analyses and showed diverse compositions of charged, polar and hydrophobic residues. Distinct sites for the shorter AOSs merged to accommodate longer AOSs. The AOSs bound dynamically to β‐LgA, as concluded from saturation transfer difference and 1 H‐ligand‐targeted NMR analyses. Molecular docking using Glide within the Schrödinger suite 2016‐1 revealed the orientation of AOSs to only vary slightly at the preferred β‐LgA binding site resulting in similar XP glide scores. The multivalency coupled with highly dynamic AOS binding with lack of confined conformations in the β‐LgA complexes may help explain the first steps toward disordered β‐LgA alginate coacervate structures.